Agent & Supplier e-Marketplace (A&S.com) / Mohammad Aiman Ismail - Ismail, Mohammad Aiman (2017)
E-marketplace is an electronic platform where buyers and sellers meet to conduct business transactions. An e-marketplace maker plays a major role in providing and managing the e-marketplace facilities for the buyers and sellers. The exchanging of product, information and money mainly occurred between the buyers and sellers. Currently, the process of dropshipping is conducted through social network and communication applications. Several constraints in conducting business through social networks and communication applications are the cumbersome interaction for personal and business use as well as the difficulties in conducting transactions among the market participants. Hence, Dropship Agents and Suppliers e-Marketplace (A&S.com) is developed to assist the agents and the suppliers to conduct business in a more systematic way. The system’s core function is focused on the interactions and transactions among the dropship agents and the suppliers. This prototype system is derived from the development process conducted by adapting the Waterfall Model of the SDLC. The methodology comprises of six sequential steps which are planning, analysis, design, development, testing and evaluation as well as the documentation phase. The prototype is scheduled to be tested and evaluated in terms of functionality and usability by three (3) expert users and thirty (30) respondents. As the result, the highest mean is 4.4 (SD=0.728) for construct satisfactory. This concludes that majority of the respondents are satisfied with A&S.com. It is hoped that A&S.com will enhance the flow of current business process for the dropship agents and their suppliers.